Fotografi Di Era Media Sosial : Studi â€œToko Memorabiliaâ€ Karya Agan Harahap - Aji Susanto Anom Purnomo (Jurnal Bahasa Rupa, 2018)
The development of photography technology in the era of social media currently contribute various problems that need to be studied and reflected. One of them is about the essence or meaning of the presence of "photography" itself. This paper reflect the essence or meaning of photography in the social media based on the theory of reading photographs "cynical phenomenology" by Roland Barthes through a case study study of "Toko Memorabilia" which is one of the social criticisms by the artist Agan Harahap. Memories Commodification and visual carnivals are two instruments of meaning that the author discovers in his critical reflection journey and will be described further through this study.